THERMAL SENSING OF HIGHORI TEMPERATURE SOLAR INSTRUMENTS, SOLAR PHOTOELECTRIC ENERGY - Xasanov Diyorjon; Qulmurodova Mohichehra; Otakuziyeva Vazirahon Usmonjonovna (American Journals, 2023)
This concertation in the article the sun water heater heat sensitive high temperature the sun of devices feel the heat. the sun photoelectric energy about data seeing developed.
Keywords: Water heater, focus distance, concentration, half conductor, current density.